Understanding Performance Appraisal Satisfaction: The Moderating Role Of Trustworthiness Toward Supervisors - Almutairi, Mohammad M S M Sh (2024)
The purpose of this study is to test the relationship between performance appraisal justice and utilization dimensions and employee satisfaction. Furthermore, this research also seeks to test the moderating effect of trustworthness toward the supervisor in this relationship.